2021
DOI: 10.1155/2021/8569225
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Graphene Quantum Dot Improved Cardiac Function in Rats with Myocardial Infarction: Morphological, Oxidative Stress, and Toxicological Evidences

Abstract: Introduction. The biocompatibility and potential application of graphene-based nanomaterials in biomedicine have been documented. The effects of polyethylene glycol-graphene quantum dots (GQDs-PEG) on cardiac function in rats with myocardial infarction (MI) were examined. Methods. Wistar rats were randomly assigned to two main groups, each consisting of sham-Veh., MI-Veh., and MI+GQDs-PEG at doses of 5, 10, and 20 mg/kg. MI was induced by the closure of the left anterior descending (LAD) coronary artery. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Subsequently, a 20 % sodium chloride solution was injected intravenously 3 times. After correcting the volume data by conductance measurement, the mice were sacrificed for tissue collection [ 16 , 17 ]. Statistical analyses were performed using PRISM ( GraphPad Software Inc) with the non-paired t -test.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, a 20 % sodium chloride solution was injected intravenously 3 times. After correcting the volume data by conductance measurement, the mice were sacrificed for tissue collection [ 16 , 17 ]. Statistical analyses were performed using PRISM ( GraphPad Software Inc) with the non-paired t -test.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo and in vitro model studies indicate they are potential antioxidants. [149][150][151] In a previous study based on dextran sulfate sodium-induced colitis in mice, GQDs showed a reduction of intestinal damage and colon inammation. The particles were not harmful to the host cells as well as bacteria.…”
Section: Reviewmentioning
confidence: 95%
“…The previous study showed that PEG-GQDs have no curative effects at 5 mg kg 21 but are effective at 10 mg kg 21 on MI. 20 Therefore, in this study, curcumin was loaded on PEG-GQDs at 5 mg kg 21 (ineffective dose) and 10 mg kg 21 (effective dose) to produce Cur-PEG-GQDs. Each mg of PEG-GQDs loads 0.003 mg of curcumin, so Cur-PEG-GQDs at the dose of 10 mg kg 21 have twice the concentration of Cur.…”
Section: Treatment With Cur Peg-gqds and Cur-peg-gqdsmentioning
confidence: 99%
“…19 The beneficial effects of polyethylene glycol-graphene quantum dots (PEG-GQDs) on MI injuries through oxidative stress reduction have been demonstrated. 20 Considering their physicochemical properties, small size, various functional groups (epoxy, hydroxyl, and carboxyl), and extensive surface, they are excellent candidates for drug loading and delivery to particular anatomical regions in the body. 21 It has been demonstrated that GQDs release loaded drugs in a controlled manner.…”
Section: Introductionmentioning
confidence: 99%